(untitled) - Betsis, Andrew (Thành phố Hồ Chí Minh, 2014)
It contains in-depth strategies for developing students' listening skills. All the different tasks of the IELTS Listening section, such as maps, iagrams, flowcharts, multiple-choice, gap filling, true-false, matching etc. are included
Keywords: Vocabulary,English language,Tiếng Anh,Từ vựng,Tiếng Anh,English language; Examinations,Nghe,Kỳ thi,Listening